Acute effects of an instructional movie on drop jump performance and lower limb kinematic and kinetic variables - Yoshida, T.; Zushi, A.; Yoshida, Y.; Maemura, H.; Ono, S.; Tanigawa, S. (Frontiers in Virtual Reality, 2024)
OBJECTIVES Drop jumping (DJ) is a typical exercise of plyometric training in which the state before takeoff (preset phase) influences the force exertion of the lower limbs during takeoff, as well as performance variables. This study aimed to examine the effects of watching an instructional movie during the preset phase on the performance and lower limb kinematic and kinetic variables during plyometric training.METHODSː Fourteen participants (age, 21.9 ± 2.1 years; height, 175.6 ± 2.6 cm; weight, 70.7 ± 4.9 kg) were enrolled in this study. Seven participants with a high rebound jump (RJ) index under normal conditions were classified into the higher group. Seven participants with a low RJ index were classified into the lower group. DJs were performed under normal conditions and under the movie condition (DJ immediately after watching the instructional movie during the preset phase). Performance and kinematic and kinetic variables of the lower limb joints were measured.RESULTSː Compared with the normal condition, the movie condition was associated with a significantly higher RJ index, lesser degree of knee flexion (p < 0.011), and significantly larger concentric torque (p < 0.018) of the ankle. An interaction effect was observed for the eccentric torque (p < 0.025) and positive power (p < 0.004) of the ankle, which were significantly greater in the higher group under the movie condition. This is a provisional file, not the final typeset article CONCLUSIONSː Watching an instructional movie during the preset phase improves the movement and force production of the ankle and knee joint, which, in turn, improves the DJ performance. However, the effects may be more pronounced in participants with a higher RJ index. 1 Condition Group Condition × group 12.674 2.979 6.279 0.004 ** 0.110 0.028 *